Flail Chest: A Literature Review - Alvian Mohamad Yapanto (Green Publisher Indonesia, 2022)
This study aims to make a review about flail chest management so this can be a simple and useful reference for surgeons to make a decision for flail chest management decisions. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library studies) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. From the results of research and discussion concluded that early surgical stabilization of rib fracture has better outcome in the cases of ribs fracture which are severe enough